The enhancement of rapidly quenched galaxies in distant clusters at 0.5 < z < 1.0. Issue 1 (6th February 2018) - Socolovsky, Miguel; Almaini, Omar; Hatch, Nina A; Wild, Vivienne; Maltby, David T; Hartley, William G; Simpson, Chris
Abstract: We investigate the relationship between environment and galaxy evolution in the redshift range 0.5 < z < 1.0. Galaxy overdensities are selected using a friends-of-friends algorithm, applied to deep photometric data in the Ultra-Deep Survey field. A study of the resulting stellar mass functions reveals clear differences between cluster and field environments, with a strong excess of low-mass rapidly quenched galaxies in cluster environments compared to the field. Cluster environments also show a corresponding deficit of young, low-mass star-forming galaxies, which show a sharp radial decline towards cluster centres. By comparing mass functions and radial distributions, we conclude that young star-forming galaxies are rapidly quenched as they enter overdense environments, becoming post-starburst galaxies before joining the red sequence. Our results also point to the existence of two environmental quenching pathways operating in galaxy clusters, operating on different time-scales. Fast quenching acts on galaxies with high specific star formation rates, operating on time-scales shorter than the cluster dynamical time (<1 Gyr). In contrast, slow quenching affects galaxies with moderate specific star formation rates, regardless of their stellar mass, and acts on longer time-scales (≳ 1 Gyr). Of the cluster galaxies in the stellar mass range 9.0 < log ( M /M⊙ ) < 10.5 quenched during this epoch, we find that 73 per cent were transformed through fast quenching, while the remaining 27 per cent followed the slow quenching route.